2017
DOI: 10.1093/treephys/tpx024
|View full text |Cite
|
Sign up to set email alerts
|

Transpiration of Eucalyptus woodlands across a natural gradient of depth-to-groundwater

Abstract: 1Water resources and their management present social, economic and environmental 2 challenges, with demand for human consumptive, industrial and environmental uses 3 increasing globally. However environmental water requirements, that is, the allocation of 4 water to the maintenance of ecosystem health, are often neglected or poorly quantified. Further, transpiration by trees is commonly a major determinant of the hydrological balance 6 of woodlands but recognition of the role of groundwater in hydrological bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Thus, although we successfully implemented a drought that dried the soils from the surface to 1 m depth, the trees successfully avoided acute physiological drought stress by reducing growth and transpiration rates while also acquiring deeper soil water. Previous studies have shown that groundwater use enables vegetation to mitigate production declines under conditions of surface moisture limitation (Baldocchi et al, 2010;Barbeta et al, 2015), and several eucalypt species are well-known users of groundwater (Mensforth et al, 1994;Pfautsch et al, 2011Pfautsch et al, , 2015Eamus et al, 2015;Zolfaghar et al, 2017). Furthermore, Koirala et al (2017) demonstrated correlations between GPP and groundwater table depth that were present over c. 70% of the vegetated surface of the Earth, suggesting that vegetation-groundwater interactions are common and globally relevant.…”
Section: Effects Of Drought On C Allocationmentioning
confidence: 97%
“…Thus, although we successfully implemented a drought that dried the soils from the surface to 1 m depth, the trees successfully avoided acute physiological drought stress by reducing growth and transpiration rates while also acquiring deeper soil water. Previous studies have shown that groundwater use enables vegetation to mitigate production declines under conditions of surface moisture limitation (Baldocchi et al, 2010;Barbeta et al, 2015), and several eucalypt species are well-known users of groundwater (Mensforth et al, 1994;Pfautsch et al, 2011Pfautsch et al, , 2015Eamus et al, 2015;Zolfaghar et al, 2017). Furthermore, Koirala et al (2017) demonstrated correlations between GPP and groundwater table depth that were present over c. 70% of the vegetated surface of the Earth, suggesting that vegetation-groundwater interactions are common and globally relevant.…”
Section: Effects Of Drought On C Allocationmentioning
confidence: 97%
“…The physiological stress intensity experienced by a tree is determined by a set of morpho-physiological and structural features associated with water absorption, conduction, and loss (Cruiziat et al, 2002 ; Addington et al, 2006 ). Facing a water stress, initially the plants are reported to reduce its stomatal conductance with gas exchange consequences (Eamus et al, 2013 ), what has been studied under natural conditions using stable carbon isotopes in organic matter (Zolfaghar et al, 2017 ). In the medium-to-long term, the trees make anatomical-structural modifications leading at maintaining either their water transport efficiency (water transport capacity) and/or safety (increased cavitation resistance) of their hydraulic systems, existing a trade-off between these hydraulic strategies (Tyree et al, 1994 ; Maherali et al, 2004 ; Sperry et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…It should also have a greater investment in root growth (De Micco and Aronne, 2012 ) and conductive tissue, as well as lower investment in above-ground biomass (Gotsch et al, 2010 ; Gehring et al, 2016 ). Leaf area should be reduced via defoliation (Rood et al, 2000 ; Zolfaghar et al, 2017 ), and leaf mass per unit area should be increased, thereby increasing wilting resistance (Bucci et al, 2004 ; Poorter et al, 2009 ; Shadwell and February, 2017 ). The deployment of these adjustments should keep a relatively high rate of transpiration per unit leaf area, maintaining gas exchange, however, exposure to lower water potentials could lead to generalized cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in foliar Δ 13 C represents 15 decreased access to water and increasing WUE i (Leffler and Evans, 1999;Zolfaghar et al, 2014;Zolfaghar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%